Digital transformation in SMEs: Understanding its determinants and size heterogeneity - Clemente-Almendros, José Antonio; Nicoara-Popescu, Dorina; Pastor-Sanz, Iván (Technology in Society, 2024)
Digital transformation plays a vital role in the success of firms, especially for small and medium-sized enterprises (SMEs). The business landscape is becoming more challenging for small businesses and they must navigate this complexity by adopting digitalization. However, many of them fail in this process. Our study aims to understand the main determinants of digital transformation, and the effect of size heterogeneity within SMEs. To this end, we apply the resource-based view, the technology-organization-environment framework and the technology acceptance model to a statistically representative sample of Spanish SMEs. We show that the manager's academic background, internationalization and firm size have a positive impact on digital adoption. Knowledge resulting from professionalization and an international context plays a critical role in overcoming SMEs' limitations and achieving digital transformation. Moreover, the positive effect of size is moderated by the levels of managerial education and internationalization. We go beyond the comparison between SMEs and large companies, by providing evidence about size heterogeneity within SMEs. Our findings provide valuable guidance for SMEs' digital transformation journeys, encouraging managers to embrace new knowledge and capabilities. Additionally, SME growth can facilitate digital transformation. Policymakers should develop programs aimed at promoting SME professionalization and international expansion.
Keywords: size heterogeneity; digital transformation; SMEs